Information Literacy Skills: A Strategic Imperative for Librarians in the Digital Age - Amogu , Uma Kalu; Obi, Hilda Eno (MiddleBelt Journal of Library and Information Science, 2015)
The Digital Age has come with a lot of changes in the ways and manner information is handled and for librarians to perform their duties effectively, efficiently and competently, they must respond positively to the changes brought about by the new trend in information handling. The paper aims at discussing the information literacy skills needed by librarians in performing their professional duties in the new era called the “Digital Age”. The paper also looked at the various eras, which civilization has passed through before the Digital Age; concept of information literacy; the need and importance of information literacy to librarians and the approaches to information literacy. It highlights the information literacy skills needed by librarians namely skills on need for information; understanding availability skills; skills on information location; skills on result evaluation; skills on result exploitation; skills on ethics and responsibility of use of information; skills on sharing or communicating information and skills on managing findings. The paper concludes by highlighting the urgency and strategic imperativeness of librarians in acquiring information literacy skills, if they must be remain central to information provision in the Digital Age.